(untitled) (Jurnal EurekaMatika, 2019)
Gemini said Life insurance is an insurance policy that provides a specific sum of money upon the death of the insured to family members or beneficiaries as specified in the insurance policy terms. The insured party is required to pay a certain amount in each period until the contract term expires, as agreed upon by both parties. Annuity is a series of periodic payments in a specific amount and over a specific duration. Meanwhile, a premium is a payment made in each period in a specific amount and over a specific duration. This article discusses how to determine the premiums for term life insurance, pure endowment insurance, and endowment insurance, as well as the design of their application programs. Based on the research conducted, it can be concluded that annuities and benefits can be used to calculate insurance premiums. This application program was developed using the Python programming language. Keywords: Annuity, Benefit, Insurance, Policy, Premium. ABSTRAK Asuransi jiwa adalah asuransi yang memberikan pembayaran sejumlah uang tertentu atas kematian tertanggung kepada anggota keluarga atau orang yang berhak menerimanya sesuai dengan ketentuan dalam polis asuransi. Pihak tertanggung wajib membayarkan sejumlah uang setiap periode sampai jangka waktu kontrak selesai sesuai kesepakatan kedua belah pihak. Anuitas adalah sederet pembayaran berkala dalam jumlah tertentu dan selama waktu tertentu. Sedangkan premi adalah suatu pembayaran yang dilakukan setiap periode dalam jumlah tertentu yang dilakukan setiap periode tertentu dan selama waktu tertentu. Pada Artikel ini akan membahas mengenai bagaimana menentukan premi asuransi jiwa berjangka, asuransi tabungan berjangka, dan asuransi dwiguna berjangka serta perancangan program aplikasinya. Berdasarkan penelitian yang telah dilakukan dapat disimpulkan bahwa anuitas dan benefit dapat digunakan untuk melakukan perhitungan premi asuransi. Program aplikasi ini dibuat menggunakan bahasa pemrograman Python.